Mesenchymal Stem Cells Regulate Type 2 Innate Lymphoid Cells via Regulatory T Cells through ICOS-ICOSL Interaction. (19th March 2021) - Fan, Xingliang; Xu, Zhi-Bin; Li, Cheng-Lin; Zhang, Hong-Yu; Peng, Ya-Qi; He, Bi-Xin; Liu, Xiao-Qing; Chen, De-Hua; Chen, Dong; Akdis, Cezmi A.; Fu, Qing-Ling
Abstract: Group 2 innate lymphoid cells (ILC2s) are recognized as key controllers and effectors of type 2 inflammation. Mesenchymal stem cells (MSCs) have been shown to alleviate type 2 inflammation by modulating T lymphocyte subsets and decreasing TH 2 cytokine levels. However, the effects of MSCs on ILC2s have not been investigated. In this study, we investigated the potential immunomodulatory effects of MSCs on ILC2s in peripheral blood mononuclear cells (PBMCs) from allergic rhinitis patients and healthy subjects. We further investigated the mechanisms involved in the MSC modulation using isolated lineage negative (Lin − ) cells. PBMCs and Lin − cells were cocultured with induced pluripotent stem cell-derived MSCs (iPSC-MSCs) under the stimulation of epithelial cytokines IL-25 and IL-33. And the ILC2 levels and functions were examined and the possible mechanisms were investigated based on regulatory T (Treg) cells and ICOS-ICOSL pathway. iPSC-MSCs successfully decreased the high levels of IL-13, IL-9, and IL-5 in PBMCs in response to IL-25, IL-33, and the high percentages of IL-13 + ILC2s and IL-9 + ILC2s in response to epithelial cytokines were significantly reversed after the treatment of iPSC-MSCs. However, iPSC-MSCs were found directly to enhance ILC2 levels and functions via ICOS-ICOSL interaction in Lin − cells and pure ILC2s. iPSC-MSCs exerted their inhibitory effects on ILC2s via activating Treg cells through ICOS-ICOSL interaction. The MSC-induced Treg cells then suppressed ILC2s by secreting IL-10 in the coculture system. This study revealed that human MSCs suppressed ILC2s via Treg cells through ICOS-ICOSL interaction, which provides further insight to regulate ILC2s in inflammatory disorders.